Awjedni: A Reverse-Image-Search Application - Al-Lohibi, Hanaa; Alkhamisi, Tahani; Assagran, Maha; Aljohani, Amal; Aljahdali, Asia Othaman (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2020)
The abundance of photos on the internet, along with smartphones that could implement computer vision technologies allow for a unique way to browse the web. These technologies have potential used in many widely accessible and globally available reverse-image search applications. One of these applications is the use of reverse-image search to help people finding items which they're interested in, but they can’t name it. This is where Awjedni was born. Awjedni is a reverse-image search application compatible with iOS and Android smartphones built to provide an efficient way to search millions of products on the internet using images only. Awjedni utilizes a computer vision technology through implementing multiple libraries and frameworks to process images, recognize objects, and crawl the web. Users simply upload/take a photo of a desired item and the application returns visually similar items and a direct link to the websites that sell them.